Studi Kualitatif Harapan Perawat terhadap Pelayanan Hemodialisa di Masa Pandemi Covid-19 - Ethic Palupi; Santahana Febrianti; Elmi Yatha Sartika; Monika Oktaviani Dongoran; Shintia Christ Damayanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
During the Covid-19 pandemic, there were still many patients and their families in the hemodialysis room who ignored health protocols. So research is needed that aims to find out the description and expectations of nurses for hemodialysis services during the Covid-19 pandemic. This study is included in a qualitative research with in-depth interviews, which analyzes the results of the interviews by coding, determining the categories, and determining the themes of the interview results. The results of interviews with 6 hemodialysis unit nurses at private hospitals in the Yogyakarta area found 55 codes, 17 categories, and 4 themes. It was concluded that there is management of health protocols in the hemodialysis room; there is screening of patients, attendants and nurses; there is arrangement of place, arrangement of schedules, and arrangement of human resources.Keywords: nurse's expectation; hemodialysis services; the Covid-19 pandemic ABSTRAK Di masa pandemi Covid-19, di ruang hemodialisa masih banyak pasien dan keluarga pasien yang mengabaikan protokol kesehatan. Maka diperlukan penelitian yang bertujuan untuk mengetahui gambaran dan harapan perawat terhadap pelayanan hemodialisa di masa pandemi Covid-19. Studi ini termasuk dalam penelitian kualitatif dengan wawancara mendalam, yang menganalisis hasil wawancara dengan koding, menentukan kategori, dan menentukan tema dari hasil wawancara. Hasil wawancara dengan 6 perawat unit hemodialisa di rumah sakit swasta di wilayah Yogyakarta mendapatkan 55 kode, 17 kategori, dan 4 tema. Disimpulkan bahwa ada penatalaksanaan protokol kesehatan di ruang hemodialisa; ada skrining terhadap pasien, penunggu, dan perawat; ada penataan tempat, penataan jadwal, dan penataan sumberdaya manusia.Kata kunci: harapan perawat; pelayanan hemodialisa; pandemi Covid-19